Quasinormal modes of magnetized black hole - Bobur Turimov; Bobir Toshmatov; Bobomurat Ahmedov; Zdeněk Stuchlík (Physical Review D (American Physical Society), 2019)
We investigate a charged, massive scalar field around a static, spherically symmetric black hole immersed into an external asymptotically uniform magnetic field B. It is shown that for given multipole number ℓ there are numbers of modes due to the Zeeman effect appearing by an interaction of the external magnetic and charged scalar fields introducing an effective mass of the scalar field where m is the azimuthal number and q is the charge coupling constant. We calculate threshold value of effective mass in which quasinormal modes are arbitrarily long lived and beyond that value quasinormal modes vanish. In the case of quasinormal modes are longer lived with larger oscillation frequencies. Whenever, magnetic and massive scalar fields satisfies condition, an instability appears, i.e., if or there is an instability for the values of azimuthal number or respectively.
Keywords: quasinormal modes; magnetized black hole; charged scalar field; Zeeman effect; effective mass; mode instability; type of access: open access